Effect of TiO2 as an additive on the sintering performance of Sm-doped CeO2-based electrolyte for solid oxide fuel cells - Sun, Xuzhuo; Deng, Shuailei; Xia, Yunyun; Li, Bo; Tian, Ye; Chen, Jing (Frontiers in Chemistry, 2022)
In this work, TiO2 was selected as an additive to the Sm0.2Ce0.8O2-δ (SDC) electrolyte and its influence on the electrolyte properties were investigated. The tetrabutyl titanate hydrolysis product was introduced into the SDC samples as a source of TiO2. The lattice contraction of SDC was observed by XRD when the smaller ionic radius Ti4+ (0.605Å) were substituted for Ce4+ (0.97 Å). XRD analysis shows that the doping content of the TiO2 in SDC should be limited to 1 wt% to maintain the single-phase cubic fluorite structure of the SDC and avoid impurity phases. SEM characterizations suggest that the addition of TiO2 significantly promoted the grain growth and the sintering activity, especially when doping with 0.5 wt% of TiO2. The electrochemical measurements reveal that the addition of TiO2 had little effect on the conductivity of SDC samples, which was 0.0306 S cm−1 at 700°C. This study shows that 0.5 wt% TiO2 doping can effectively improve the sintering activity without reducing the SDC performance.